The Uncanny Wall. (1st January 2011) - Tinwell, Angela; Grimshaw, Mark; Williams, Andrew
This paper proposes that increasing technological sophistication in the creation of realism for human-like, virtual characters is matched by increasing technological discernment on the part of the viewer. One of the goals for achieving a realism that is believable for virtual characters is to overcome the Uncanny Valley where perceived strangeness or familiarity is rated against perceived human-likeness. Empirical evidence shows that the Uncanny can be applied to virtual characters, yet implies a more complex picture than the shape of a deep valley with a sharp gradient as depicted in Mori's original plot of the Uncanny Valley. Our results imply that: (1) perceived familiarity is dependent upon a wider range of variables other than appearance and behaviour and (2) for realistic, human-like characters, the Uncanny Valley is an impossible traverse, is not supported fully by empirical evidence and the concept is better replaced with the notion of an Uncanny Wall.